Ultraportable Oxygen Concentrator Use in U.S. Army Special Operations Forward Area Surgery: A Proof of Concept in Multiple Environments. Issue 1 (1st January 2017) - Rybak, Michael; Huffman, Lynn C.; Nahouraii, Richard; Loden, John; Gonzalez, Marcos; Wilson, Ramey; Danielson, Paul D.
ABSTRACT: Introduction: A limitation to surgical care in an austere environment is the supply of oxygen to support mechanical ventilation and general anesthesia. Portable oxygen concentrators (OCs) offer an alternative to traditional compressed oxygen tanks. Objectives: We set out to demonstrate that a low-pressure OC system could supply the mechanical ventilation needs in an austere operating environment. Methods: An ultraportable OC (SAROS Model 3000, SeQual Technologies, Ball Ground, Georgia) was paired with an Impact 754 ventilator (Impact Instrumentation, West Caldwell, New Jersey) to evaluate the delivered fraction of inspired oxygen (FiO2 ) to a test lung across a range of minute ventilations and at altitudes of 1, 200 and 6, 500 feet above sea level. Results: The compressor-driven Impact ventilator was able to deliver FiO2 at close to 0.9 for minute ventilations equal to oxygen flow. Pairing two OCs expanded the range of minute ventilations supported. OCs were less effective at concentrating oxygen at higher altitudes. Conclusions: These results demonstrate that low-pressure, ultraportable OCs are capable of delivering high FiO2 during mechanical ventilation in austere locations at both low and high altitudes. Ultraportable OCs could therefore be sufficient to support forward area surgical procedures and positively impact logistics.